Zur Entwicklung des Endoparasiten Misocyclops pini Kieffer (Proctotrupoidea: Scelionidae) und seiner Einsatzmöglichkeit gegen die Kiefernnadelgallmücke Thecodiplosis brachyntera Schwaegrichen (Diptera: Cecidomyiidae). - Fankhänel, Heinz; Zeletzki, Christel (Contributions to Entomology = Beiträge zur Entomologie, 1964)
Data about the larva development of the greatly specialized endoparasite Misocyclops pini Kieffer are given. In the years from 1959 to 1963 this scelionid was able to check mass invasions of the pine needle gall midge Thecodiplosis brachyntera Schwaegrichen in some heavily infested pine stands of the State Forest Administrations of Neuruppin, Kyritz, and Roßlau. It is most suitable for an early estimate of the degree of parasite attack on the gall midge population to keep hosts and parasites for hibernation in gauze bags under open area conditions. Possibilities of moving the ichneumon flies within a given area for purposes of biological control of the pine needle gall midge are discussed.